Ruang Lingkup Penataan Ruang dalam Pembangunan Pemukiman Berkelanjutan di Wilayah Ibu Kota Negara Nusantara - Miftah, Farrah (Universitas Batanghari Jambi, 2025)
Sustainable development in the Capital City of Indonesia which was previously in DKI Jakarta which is now moved to the Capital City of the Archipelago located in the East Kalimantan Region. The goal of sustainable development is closely related to the mission of equitable development in Indonesia. Referring to the provisions of Law Number 3 of 2022 concerning the Capital City, this sustainable development is planned using environmentally friendly materials so that it will not damage the surrounding environment considering that the potential for natural resources in the IKN area is quite large and has the potential to be developed. This study focuses on sustainable development, especially regarding settlements, immigrant communities and the surrounding area as a direct impact of development in the IKN have the right to get a decent place to live, be protected, and not reduce the value of the potential natural resources in it.